Molecular epidemiology of Clostridioides difficile isolates in a non-outbreak setting at a comprehensive cancer center - Neha Mehta; Jennifer M. Harrington; Meghan A. Wallace; Jillianna M. Wasiura; Carey-Ann D. Burnham; Katherine M. Mullin; Brahm H. Segal; Nikolaos G. Almyroudis (Cambridge University Press, 2023)
Ribotyping was performed on Clostridioides difficile isolates from patients with malignancies. Thirty-one (27.9%) isolates from 111 episodes of colitis were recovered representing 14 ribotypes with 25 (80.6%) belonging to 6 ribotypes (014/020, 1/VPI/077/087, 05/015, 015/046, 05/053, 106/174). We identified three novel ribotypes with 1 carrying gene encoding for binary toxin.